THE SYSTEMATIC REVIEW OF NON-OPIOID ANALGESICS IN ADULTS AFTER MAJOR SURGERY - Nurochman Sidik, Fajar; Muhammad Suharyo, Dhimas; Solehudin, Hipni; Lesmana Putri, Fitria (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Following surgery, chronic postsurgical discomfort is frequent. Finding non-opioid analgesics that may be able to stop persistent pain following surgery is crucial, even if these trials frequently lack sufficient funding.Aims : This systematic review is to review the effects of non-opioid analgesics in adults after major surgeryMethods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SCIENCE DIRECT, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 234 articles, whereas the results of our search on SCIENCE DIRECT brought up 803 articles. The results of the search conducted for the last year of 2014 yielded a total 67 articles for PubMed and 29 articles for SCIENCE DIRECT. In the end, we compiled a total of 6 papers, 5 of which came from PubMed and 1 of which came from SCIENCE DIRECT. We included six research that met the criteria.Conclusion: In summary, this systematic review contains the postoperative outcomes in patients after treated with intravein non opioid analgetics after surgery than in controls in terms of 24 hours post operative of opioid use, the pain score, hopitalization perior and the occurrence of opioid related adverse events.